Functional α-tropomyosin produced in Escherichia coli: A dipeptide extension can substitute the amino-terminal acetyl group - Monteiro, Patrícia Brant; Lataro, Renata Cristina [UNESP]; Ferro, Jesus Aparecido [UNESP]; De Castro Reinach, Fernando (My University, 1994)
Unlike the muscle protein, α-tropomyosin expressed in Escherichia coli does not bind actin, does not exhibit head-to-tail polymerization, and does not inhibit actomyosin ATPase activity in the absence of troponin. The only chemical difference between recombinant and muscle tropomyosins is that the first methionine is not acetylated in the recombinant protein (Hitchcock-De-Gregori, S. E., and Heald, R. W. (1987) J. Biol. Chem. 262, 9730-9735). We expressed three fusion tropomyosins in E. coli with 2, 3, and 17 amino acids fused to its amino terminus. All three fusions restored actin binding, head-to-tail polymerization, and the capacity to inhibit the actomyosin ATPase to these unacetylated tropomyosins. Unlike larger fusions, the small fusions of 2 and 3 amino acids do not interfere with regulatory function. Therefore the presence of a fused dipeptide at the amino terminus of unacetylated tropomyosin is sufficient to replace the function of the N-acetyl group present in muscle tropomyosin. A structural interpretation for the function of the acetyl group, based on our results and the coiled coil structure of tropomyosin, is presented.